Analysis of the Potential for Alternative Fuels Refused Derived Fuel from Waste Briquettes at the Sidoarjo Regency Final Disposal Site - Oktavia, Lily; Achmad Ramadhan (Journal of Research and Technology, 2022)
The Griyo Mulyo Jabon Final Waste Processing Site (TPA) in Sidoarjo Regency with a waste generation reached 350 tons/day had the potential to be processed into raw material for Refused Derived Fuel (RDF). RDF fuel had come from waste residue briquettes contained the composition of paper, wood, cloth, rubber, and plastic (4K1P). Briquettes that can be used as raw materials for RDF were those that have characteristics according to SNI standards. This study aimed to determine the percentage of the composition of briquettes that have the potential to produce RDF and the standard quality of the resulting RDF. The reseach was conducted by taking waste samples every week four times with variations in detention time of 2, 4 and 6 hours.a. The method of calculating the value of RDF standard quality was in accordance with SNI 01-6235-2000 with the parameters analyzed were water content, ash content, volatile/steam content and calorific value. The results showed that the best briquette composition produced from 4K1P waste residue was in samples with a composition of 20% wood, 10% paper, 10% rubber/fabric, and 60% plastic. The best quality briquettes with 5.5% moisture content, 4.9% ash content, 15.9% steam content, and calorific value 8996 cal/gram.